Estudio geológico-estructural y plan de seguridad minera, en el área minera "Los Cuenca" ubicada en la parroquia Torata, cantón Santa Rosa, provincia de El Oro. - León Peralta, Angélica Gabriela (2015)
Through the implementation of renewed and current methods that allow the interrelationship between stages of field and office was able to obtain information on the various mining operations and activities inside and outside the mining area "Los Cuenca", in addition to that, the use and application of advanced techniques such as geographic information systems (GIS) and allowed to process all the information collected in the field, obtaining as final results the development of databases where the structural topography and geology shown at small scales and easy appreciation for the reader. In addition to this database, the results of its analysis on issues of mine safety and conditions provided by the mine during the performance of activities of their employees is also shown, that the ultimate goal of implementing a Mining Safety Plan to help preserve the physical and psychological integrity of workers.